Hematic polyserositis - Oliveira Pedro, Ana J.; Ribeiro, Susana; Alvoeiro, Lurdes; Branco, Rui; Neto, Fernando; Távora, Isabel; Coutinho, João; Pimentel, A. (Portuguese Journal Internal Medicine, 1995)
We present a case of a sixty-two years old retired stevedore male patient with a two years clinical course of hematic serosal effusion (pleural, pericardial and peritoneal). The effusions which did not recur after drainage had 70 to 80% of mesotelial cells. The peritoneal effusion was collected in cystic cavities.The hypothesis of cystic mesothelioma, supported by the inexistence of malignant mesothelial cells in the peritoneum, seems the most probable.